Subsaturating Ribulose-1,5-Bisphosphate Concentration Promotes Inactivation of Ribulose-1,5-Bisphosphate Carboxylase/Oxygenase (Rubisco) (Studies Using Continuous Substrate Addition in the Presence and Absence of Rubisco Activase). - Portis, A. R. (1995)
We developed a continuous-addition method for maintaining subsaturating concentrations of ribulose-1,5-bisphosphate (RuBP) for several minutes, while simultaneously monitoring its consumption by ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco). This method enabled us to observe the effects of subsaturating RuBP and CO2 concentrations on the activity of Rubisco during much longer periods than previously studied. At saturating CO2, the activity of the enzyme declined faster when RuBP was maintained at concentrations near its Km value than when RuBP was saturating. At saturating RuBP, activity declined faster at limiting than at saturating CO2, in accordance with previous observations. The most rapid decline in activity occurred when both CO2 and RuBP concentrations were subsaturating. The activity loss was accompanied by decarbamylation of the enzyme, even though the enzyme was maintained at the same CO2 concentration before and after exposure to RuBP. Rubisco activase ameliorated the decline in activity at subsaturating CO2 and RuBP concentrations. The results are consistent with a proposed mechanism for regulating the carbamylation of Rubisco, which postulates that Rubisco activase counteracts Rubisco's unfavorable carbamylation equilibrium in the presence of RuBP by accelerating, in an ATP-dependent manner, the release of RuBP from its complex with uncarbamylated sites.